Le regret d’avoir déserté : une posture du soldat au XVIIIe siècle (France) - Naoko Seriu (Nuevo mundo - Mundos Nuevos, 2006)
Regretting desertion : an attitude for the soldier in the XVIIIth century (France)In order to fight desertion, the French army, from 1775, grants a couple of « days for regret ». During this period, the soldier is entitled to voluntarily come back to his regiment without being punished as a deserter. To take advantage of this opportunity, deserters can surrender to the police, but they have also the possibility to express this state of mind after they failed to escape, or even only after they have been arrested, at the time of cross-examination. If many try to benefit from this system, it helps establish a connivance with the authority. Hence, the reasons for deserting put forward are said to be linked to some kind of personal disorder : drunkness, blunder, or ‘imagination’. The violence or the injustice of the military institution, so often denounced by other deserters, are not incriminated. In the framework of the psychologization of desertion, a new relationship based on consent is established between the individual and the institution.